Pengembangan E-Instrumen untuk Menguji Model Mental Siswa pada Materi Larutan Elektrolit dan Non Elektrolit - Yulia Widayanti (Edukimia, 2021)
The purpose of this study is to design an instrument that can be used to determine students mental models in electrolyte and non-electrolyte solutions. Students do not have complete understanding of electrolyte and non-electrolyte solutions topic. It takes an instrument that can measure students mental models, which can then be used to find out why students do not have complete understanding of electrolyte and non-electrolyte solutions topic. The research method used is the RnD method with a 4D model. The research steps consist of define, design and development. The results of this study are e-instruments that can be used to measure students mental models on electrolyte and non-electrolyte solutions. The average results of the instrument feasibility from material experts and teacher experts were 89 percent and 83 percent, namely worthy with very good predicate and good predicate. These results indicate that the designed instrument is feasible to use. The instrument designed only reached the validation stage due to lack of time in research.